2022
DOI: 10.1002/tesj.652
|View full text |Cite
|
Sign up to set email alerts
|

English language development specialists' views on emergency remote teaching

Abstract: In March 2020, the COVID-19 pandemic disrupted education across the globe. In the United States, many local education agencies (LEAs) rapidly transitioned to delivering instruction virtually or with physical assignment packets. Hodges, Moore, Lockee, Trust, and Bond (2020) called this emergency remote teaching: "a temporary shift of instructional delivery to an alternate delivery mode due to crisis circumstances" (para. 5). This emergency remote teaching (ERT) was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…An important dimension of working with CLDLs is scaffolding and differentiating curriculum and instruction for students’ cultural and linguistic needs (Leider & Tigert, 2022; Lucas & Villegas, 2010a, 2010b; Paris & Alim, 2017). However, although 57 position statements address content and instruction, most position statements did not explicitly name the instructional needs of CLDLs (NCTM = 10, NCSS = 14, NSTA = 20), with NCTE standing out as the exception with only two position statements that did not do so.…”
Section: Resultsmentioning
confidence: 99%
“…An important dimension of working with CLDLs is scaffolding and differentiating curriculum and instruction for students’ cultural and linguistic needs (Leider & Tigert, 2022; Lucas & Villegas, 2010a, 2010b; Paris & Alim, 2017). However, although 57 position statements address content and instruction, most position statements did not explicitly name the instructional needs of CLDLs (NCTM = 10, NCSS = 14, NSTA = 20), with NCTE standing out as the exception with only two position statements that did not do so.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies report on how digital divides have affected ESOL classes or learning, some predating the COVID‐19 pandemic and some motivated by the pandemic situation. A survey of elementary and secondary English language teachers during COVID‐19 found a disproportionate negative effect of emergency remote teaching on multilingual students, with disparities in access to technology and online instruction despite districts' efforts to distribute devices to families (Leider & Tigert, 2022). The researchers concluded that institutional structures and policies could be more equity‐minded, for example including plans for translation/interpretation and family engagement that do not place a greater burden on ESOL teachers by asking them to take on those tasks.…”
Section: Esol Digital Divides and Digital Literaciesmentioning
confidence: 99%